Imaging Hyperreflective Foci as an Inflammatory Biomarker after Anti-VEGF Treatment in Neovascular Age-Related Macular Degeneration Patients with Optical Coherence Tomography Angiography. (4th February 2021) - Wu, Jing; Zhang, Chaoyang; Yang, Qian; Xie, Hai; Zhang, Jingting; Qiu, Qinghua; Liu, Kun; Luo, Dawei; Liu, Fang; Zhang, Jingfa
Abstract : Purpose . To investigate the hyperreflective foci (HRF) as an inflammatory biomarker using optical coherence tomography angiography (OCTA) in neovascular age-related macular degeneration (AMD) patients after antivascular endothelial growth factor (anti-VEGF) treatment and its association with the retinal microcapillary density. Methods . Twenty-five eyes from 25 patients with neovascular AMD were included in the study. All eyes were imaged with OCTA at baseline (M0) and after 3 consecutive injections (M3; injection performed each month) of anti-VEGF. The number of HRF in the superficial capillary plexus (SCP), deep capillary plexus (DCP), and outer retina was counted. The vascular density of the fovea, parafovea, and the whole macula, as well as the area of the foveal avascular zone (FAZ), was measured. Results . The mean interval between baseline and follow-up with OCTA was 93.08 ± 5.00 (range, 85-101) days. Compared with the baseline, the number of HRF significantly decreased in DCP (7.52 ± 3.06 vs. 3.76 ± 1.48, P < 0.01 ) and outer retina (12.04 ± 4.91 vs. 5.88 ± 3.32, P < 0.01 ) after treatment. There was no significant difference for HRF number in the SCP, the vascular density (containing foveal, parafoveal, and whole macular), and FAZ area before and after treatments. Conclusion . The number of HRF in DCP and outer retina might serve as an inflammatory biomarker in patients with neovascular AMD. The reduced HRF possibly represents the alleviation of inflammation after anti-VEGF treatment in patients with AMD.